Prevalence and Modifiable Risk Factors of NonCommunicable Diseases among Jakun Orang Asli at Tasik Chini, Pekan, Pahang - CM, Wong; D, Faiz; S, Diana Safraa; RH, Raja Mohd Azim; AR, Siti Zubaidah (IIUM Medical Journal Malaysia, 2018)
Introduction: Non-communicable disease accounted for 73% of premature death in year 2015 Malaysian national survey. The orang asli population may be affected similarly. The prevention of non-communicable diseases should start as early as modifiable risk factors prevention, as proposed by STEPWISE approach of WHO. This study aims to identify the prevalence of hypertension, diabetes mellitus and dyslipidaemia among Jakun orang asli population and examine the association with risk factors. Methods: This is a cross-sectional study analysing 72 case reports of General health screening done in year 2015. The study population was adult Jakun orang asli Tasik Chini using cluster sampling followed by simple random sampling methods. Chi Square test was used for bivariate analysis of relationship each variable has with the diseases, and binary logistic regression was used to analyse association of covariates with each disease. Results: The prevalence was 41.7% for hypertension, 25% for Diabetes mellitus, 6.9% for dyslipidaemia. Education level was significantly related to hypertension, X2 = 11.565 (1), p =0.001; obesity was significantly related to diabetes, X 2 = 8.333 (1), p=0.004. After adjusted for covariates, low education level has 13.379 odds of getting hypertension. Obesity has 7.384 odds of getting diabetes mellitus; female gender has higher odds of getting dyslipidaemia while younger age, physically active and not smoking are protective factors. Conclusion: Higher prevalence of hypertension and diabetes mellitus was found among Tasik Chini orang asli population. Lower sociodemographic characteristics and unhealthy lifestyle factors are associated with the diseases.